Income Inequality in Indonesia: Which Aspects Cause the Most? - Eny Sulistyaningrum; Alexander Michael Tjahjadi (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: This study discusses the three main aspects of inequality: the level of education attained, urban-rural area, and gender. Background Problems: Inequality is one of the fundamental economic problems in Indonesia that has the potential to cause the non-optimal distribution of resources, economic instability, and may even lead to an economic crisis. Novelty: This study provide a new perspective on the differences in findings for the aspects of gender, education, and geographic factors on income inequality Research Methods: This study uses the Theil index for decomposition analysis and quantile regression analysis to analyze each class of income, particularly in the context of income inequality factors. Finding/Results: The findings show that, male workers in the lower class have a greater income than female workers. In addition, workers with an elementary school level experience higher inequality than workers with other levels of education do. Moreover, higher inequality occurs for urban workers in both the upper and lower classes, compared to workers in rural areas. From quantile regression analysis, the results show that, income inequality between men and women is reducing. The number of completed years has less influence compared to that in earlier periods, because more and more people enter education to increase their income. Lastly, urban workers have different incomes from rural workers, though the gap is reducing. It means both urban and rural workers have greater opportunities to earn a better income. Conclusion: Gender plays an important role in income inequality. The length of education has constantly affected income inequality as well. In the context of the area, urban workers normally have higher incomes.